SISTEM PAKAR DENGAN KASUS TERAPAN DIAGNOSA JENIS DAN GANGGUAN KULIT - Agus Ramdhani Nugraha; Andri Sukmaindrayana (JURNAL MANAJEMEN INFORMATIKA (JUMIKA), 2014)
Leather is one of the human senses are located on the surface of the body. For the body, the skin has a very important function and this function is not commensurate with sepertunya thin layers. In connection with the body lying there on the surface of the skin is the first organ affected by unfavorable influence of the environment. Therefore, maintaining skin health is as important as keeping other organs.White skin is one of the attractive skin types . Not a few women who want a white skin with a reason to bear on interesting if seen . Nevertheless , behind his white skin , not necessarily always healthy . Meanwhile , many people whose skin color black , but healthy . Blacks are maintained , including an attractive skin . Any color and type , the skin should be well maintained , clean and healthy . Skin color is determined by heredity . Therefore if you are brown-skinned may not be changed to black or to white Europeans such as skin type . This can be done with the natural nature must take care is that the skin becomes healthier , cleaner and unsightly .From the above background , the authors are interested in making an application system that diagnose the type of skin and skin disorders that frequently hit , the system of diagnosis and the type of skin disorder . In making this application, the compiler uses the Delphi programming language as a tool in the process of program implementation .In general, expert systems is seeking to adopt a system of human knowledge into a computer, so the computer can resolve the problem as was done by the experts. The system is well designed in order to solve a particular problem by mimicking the work of the experts. With this expert system, the awampun can solve quite complicated problems that are actually only be solved with the help of experts. For the experts, the expert system will also help its activity as highly experienced assistant.Key Word : Skin Types, Expert Systems